From subduction to post‐collision: Early Permian‐middle Triassic magmatic records from Langshan Belt, Central Asian Orogenic Belt. (24th February 2020) - Wang, Wenlong; Teng, Xuejian; Liu, Yang; Wang, Rui; Cheng, Yinhang; Xin, Houtian; Wang, Shuqing
Abstract : We performed geochronological and geochemical analyses of granitoids in the Langshan Tectonic Belt (LTB), southwest of the Solonker suture zone, for the determination of its age, petrogenesis, and tectonic setting, which are crucial for unravelling the Permian tectonic evolution in the south‐eastern Central Asian Orogenic Belt (CAOB). It is indicated by zircon U–Pb ages together with previous ages that the Permian igneous rocks within the LTB can be grouped into two episodes. The Early‐Middle Permian ( 281–268 Ma) granitic intrusive rocks are mainly I‐type granitoids characterized by lithophile element enrichments, high‐field‐strength element depletions, and obvious negative Nb‐Ta‐Ti anomalies. These granitic intrusive rocks are further high‐K calc‐alkaline, arc‐related granitoids. In contrast, the Late Permian‐Middle Triassic ( 260–241 Ma) granitoids contain relatively high SiO2, Al2 O3, and Sr contents, but relatively low Y (Yb) contents and Mg# values, resembling the post‐collisional granitoids. Hf isotopic compositions of the two‐stage granitoids show similar features with both positive and negative values. The εHf( t ) values of the four samples from −2.6 to +4.8 record predominantly Meso–Neoproterozoic crust components. According to the regional geological investigations and geochemical data, we suggest that the Early‐Middle Permian arc‐like granitoids formed in continental arc setting, which represents the final stage of Paleo‐Asian Oceanic subduction, and then the Late Permian‐Middle Triassic adakitic granitoids were probably formed in a post‐collisional setting due to the final closure of the Paleo‐Asian Ocean.